Analisis Faktor Gaya Hidup Terhadap Kejadian Hipertensi Pada Kelompok Usia produktif Di Kelurahan Karang Anyar, Samarinda - Adnan Nur Jailani; Akhmad; Dora Dayu Rahma Turista; Sri Purwati (PendIPA Journal of Science Education, 2026)
The study was setback by Indonesian health survey 2023, hypertension prevalence in people ages 18 to 30.8%, the city health service of samarinda recorded 214,129 lives over 15 years old. The study was intended to get an overview of diet and physical activity and analyze the relationship between lifestyle factors and the incidence of hypertension in the productive age groups of the new coral samarinda. This type of study is an analtic observational by a case-control, it was done in the region of the Wonorejo hospital for 5 months in 2026, the sample was taken using a total sampling method with the 357 respondents, with 122 case groups and 235 control groups. Secondary data are obtained from the January-March 2026 surveillance forms and analyzed using univariates & bivariates (chi-square and calculating odds ratio (OR)). Bivariatic tests indicate lifestyle factors that have a significant relationship with the incidence of hypertension are short on fruit and vegetables (asymp. Sig = 0.007; OR = 1,845; 95% CI: 1.181-2,881) and excessive sugar consumption (asymp. Sig = 0.002; OR = 0.383; 95% CI: 0.207-0.706). Studies concluded that lack of diet in fruits and vegetables is a real risk factor that increases hypertension opportunities of 1.845. Instead, excessive sugar consumption indicates statistically protective level of risk (OR < 1).